(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
The study examined the lipid profile and serum biochemical indices of broiler chickens fed diets containing cassava peel meal palm oil sludge (CPMPOS) as a mixture replacement for maize. A total of 96 day-old broiler chicks (40g initial mean weight) of the Agrited Ros 308 strain were used in this study, which lasted for eight weeks. The chicks were assigned to three dietary treatments with replaced levels of 0, 22.5, and 25% of CPMPOS mixture for maize. Each treatment was replicated four times with eight birds per replicate using a completely randomized design (CRD). Feed and water were supplied ad libitum. At the end of the feeding trial, 10mls of blood were collected from two birds per replicate from their brachial veins into non-heparinized bottles for biochemical assay. Results were subjected to one-way ANOVA. The study revealed that CPMPOS had no significant (p>0.05) effects on the lipid profile and serum electrolytes. The study therefore recommends the use of a 25% level of CPMPOS as a replacement for maize in broiler chicken diets without fear of compromising lipid and serum biochemical assays.